Orientasi Etika, Faktor Situasional dan Pengambilan Keputusan Etis dengan Komitmen Profesional Sebagai Pemoderasi - Pradnyana Dwipa, Anak Agung Gede; Dwi Ratnadi, Ni Made; Yadnyana, I Ketut; Budiartha, Ketut (E-Jurnal Akuntansi, 2023)
This study aims to empirically prove the effect of ethical orientation and situational factors on ethical decision making of tax consultants in Bali with professional commitment as a moderating variable. The research population of tax consultant members who are registered with the Indonesian Tax Consultants Association (IKPI) for the Bali Region is 278 people. The sampling technique used is saturated sampling technique with a total sample of 278 people. The research data was collected by distributing questionnaires and processed using the Partial Least Square (SEM-PLS) tool. The results of the analysis showed that ethical orientation of idealism, current information, moral intensity had a positive effect on ethical decision-making, while the ethical orientation of relativism, risk preference had a negative effect. on ethical decision making. In addition, professional commitment weakens the influence of ethical idealism orientation on ethical decision making, professional commitment strengthens the influence of relativism ethical orientation, and the current information on ethical decision making. Meanwhile, professional commitment cannot moderate the effect of risk preference and moral intensity on ethical decision making. The implications for tax consultants are to pay more attention to their ethical orientation and to pay attention to situational factors in order to create decisions that pay attention to ethics. Keywords: Ethical Decisions; Ethics; Situational Factors; Professional Commitment